Anterior Cervical V‐Shaped Osteotomy and Fusion (ACVF) for Retro‐Corporeal Decompression Bypassing Anterior Corpus Vertebra: A Technical Note - Minghe Yao; Yaling Li; Beiyu Wang; Tingkui Wu; Kangkang Huang; Shihao Chen; Xiaoqiang Zhao; Yi Deng; Hao Liu (Orthopaedic Surgery, 2025)
ABSTRACT Objective Anterior cervical discectomy and fusion (ACDF) is a trans‐intervertebral space procedure with limited ability to treat compression at the back of the vertebral body. Anterior cervical corpectomy and fusion (ACCF) can be applied in this case, but the higher complication rates restrict its usage. This study aims to describe an ACDF‐based procedure named anterior cervical V‐shaped osteotomy and fusion (ACVF) with a long axial decompression range while preserving the intact anterior half of the vertebral body. Method Four patients with contiguous two‐level degenerative cervical myelopathy who underwent ACVF with 12‐month follow‐up were retrospectively reviewed. Intraoperatively, an electrode penetration test was conducted to verify complete decompression. Clinical outcomes were evaluated using the modified Japanese Orthopedic Association (mJOA) score and the Visual Analog Scale (VAS) score. Radiological examinations, including computed tomography (CT) and magnetic resonance imaging (MRI), were used to assess spinal cord decompression and intervertebral fusion. Results All surgeries were successfully completed with an average operative time of 182 min. Both the mJOA score and the VAS score improved at the follow‐ups postoperatively. Postoperative imaging showed thorough decompression of the spinal cord, unimpaired fusion process, and acceptable vertebral body height loss. Conclusions ACVF may be safe and effective for spinal cord direct decompression in the case of retro‐corporeal compression, with the potential to serve as a substitute for ACCF and avoid the complications associated with long‐strut grafts.